Deodorization of pig feces by actinomycetes. - Ohta, Y (1978)
Peg feces, a malodorous substance causing environmental pollution, were completely deodorized within 2 days by Streptomyces. The optimum conditions for deodorization were as follows: pH, 8.6 to 10; temperature, 35 to 40 degrees C; moisture content, 42 to 63%; and minimum amount of inoculum, 2 g of seed culture per 10 g of fresh feces. Many kinds of microorganisms were isolated from the deodorized feces, of which only actinomycetes were found to have the ability to deodorize. Two strains with strong deodorizing activity were identified as Streptomyces griseus and Streptomyces antibioticus. The low-molecular-weight fatty acids, which are the specific malodorous agents of pig feces, scarcely could be found in feces deodorized by the isolated strains. Chemical analysis showed that the deodorized feces are useful as manure.